The evaluation of program death 1 and PD-1 ligand expressions in histological subtypes of primary extranodal non hodgkin lymphoma - Mohaidin, Farhana Mohammad (2021)
Introduction: Emergence of Programmed death 1 (PD-1) and its ligands, PD-L1 immunotherapy provide new insight in the treatment modality of malignancies. The responsiveness of the patients are associated with the expressions of the PD-L1 and PD-1 protein. We aimed to evaluate the expression of PD-1 in the tumour microenvironment and PD-L1 in the tumour cells with histological subtypes of primary extranodal non-Hodgkin lymphoma (peNHL). Methodology: A retrospective cross-sectional study using 87 archived formalin fixed paraffin-embedded tissue blocks of patients diagnosed with peNHL. Samples were stained for PD-1 and PD-L1 by immunohistochemistry method and the proteins expressions were evaluated microscopically. The association between expression of the PD-1 and PD-L1 with subtypes of peNHL were statistically analysed. Results: Majority of the cases are negative expression of PD-L1 in the tumour cells (46, 52.9%), however majority are positive for PD-1 expression in the tumour microenvironment (57, 65.5%). Significant associations were found between PD-1 and PD-L1 expression with subtypes of peNHL (p<0.05) and higher expression was found in DLBCL. Conclusion: Our study, the first in Malaysia to explore expression of PD-1 and PD-L1 in peNHL, demonstrates significant association of PD-1 and PD-L1 expressions with subtypes of peNHL which may impact treatment of these patients in the future.